APLIKASI PEMBUATAN SURAT KETERANGAN DOMISILI USAHA BERBASIS WEB (Studi Kasus: Kecamatan Pancoran Mas) - Fintri Indriyani (Swabumi, 2016)
The development of small and medium enterprises in the city of Depok has been relatively rapid, there were15,067 of Micro, Small and Medium Enterprises (SMEs) spread in each district. To be registered as a place ofbusiness that is authorized and legitimate in public administration it is necessary to do the maintenance ofBusiness Domicile Permit in order to ensure such business. So much demand for business domicile permitdocuments at the district office to make the maintenance process into a long letter because of several thingsincluding the limited number of staff, limited file storage space and file storage process is not good. The mainobjective of this study is to help the District of Pancoran Mas or particularly the staff of CommunityEmpowerment part in the making of domicile of the business so that the public service can run well. The methodused for software development is the waterfall method, and the results of this research is an information systemDomicile of Business at the district office Pancoran Mas, Depok.